2001
DOI: 10.1067/mhn.2001.118693
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Health‐Related Quality of Life in Patients with Diseases of the Ear, Nose, and Throat: A Multicenter Observational Study

Abstract: ENT diseases adversely affect the HRQOL in patients visiting their otolaryngologist. Clinical and demographic variables are important considerations in the measurement of HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Four studies did not clearly state the patient diagnosis. Three of these studies were in patients undergoing sinus surgery, 30,36,42 and 1 study included patients with “rhinosinusitis or rhinitis.” 29 Two studies had a mix of patients with chronic sinusitis and acute sinusitis 28,41 . Only 2 studies included exclusively patients with acute sinusitis 40,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies did not clearly state the patient diagnosis. Three of these studies were in patients undergoing sinus surgery, 30,36,42 and 1 study included patients with “rhinosinusitis or rhinitis.” 29 Two studies had a mix of patients with chronic sinusitis and acute sinusitis 28,41 . Only 2 studies included exclusively patients with acute sinusitis 40,45 …”
Section: Resultsmentioning
confidence: 99%
“…Among the performance characteristics examined, only content validity has been partially demonstrated for 2 instruments in patients with acute sinusitis. First, Witsell et al performed a multicenter, observational study of patients in ENT clinics using the Medical Outcomes Trust Short Form‐12 to measure HRQL 28 . Two summary scores from the Short Form‐12, the Physical Component Summary and the Mental Component Summary scores, appeared to be lower in patients with acute sinusitis compared to published control populations, but no statistical comparison was reported 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Subjective measures range from those applied to the diagnosis of rhinosinusitis, such as the "major criteria" established by the 1997 Task Force, to sophisticated symptom and quality-of-life (QOL) measures, specific indices such as rhinosinusitis disability index, rhinosinusitis outcome measures or chronic sinusitis [29][30][31][32][33]. Objective tests used are nasal culture, ciliary beat frequency, rhinomanometry, acoustic rhinomanometry, olfactory testing, saccharine test, radiographic studies and nasal endoscopies [22,[34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Witsell et al [22], using the Short Form-12 (SF-12), a generic HRQL instrument, showed that patients with acute and chronic sinusitis have measurable decrements in HRQL. The decrement in emotional well-being for sinusitis patients was greater than that for patients with congestive heart failure or recent myocardial infarction.…”
Section: Effect Of Sinusitis On Healthrelated Quality Of Lifementioning
confidence: 99%